[11C]PK11195-PET Brain Imaging of the Mitochondrial Translocator Protein in Mitochondrial Disease. (1st June 2021) - van den Ameele, Jelle; Hong, Young T.; Manavaki, Roido; Kouli, Antonina; Biggs, Heather; MacIntyre, Zoe; Horvath, Rita; Yu-Wai-Man, Patrick; Reid, Evan; Williams-Gray, Caroline H.; Bullmore, Ed T.; Aigbirhio, Franklin I.; et al.
Abstract : Objective: To explore the possibilities of radioligands against the mitochondrial outer membrane translocator protein (TSPO) as biomarkers for mitochondrial disease, we performed brain PET-MRI with [ 11 C]PK11195 in 14 patients with genetically confirmed mitochondrial disease and 33 matched controls. Methods: Case–control study of brain PET-MRI with the TSPO radioligand [ 11 C]PK11195. Results: Forty-six percent of symptomatic patients had volumes of abnormal radiotracer binding greater than the 95th percentile in controls. [ 11 C]PK11195 binding was generally greater in gray matter and significantly decreased in white matter. This was most striking in patients with nuclear TYMP or mitochondrial m.3243A>G MT-TL 1 mutations, in keeping with differences in mitochondrial density seen postmortem. Some regional binding patterns corresponded to clinical presentation and underlying mutation, even in the absence of structural changes on MRI. This was most obvious for the cerebellum, where patients with ataxia had decreased binding in the cerebellar cortex, but not necessarily volume loss. Overall, there was a positive correlation between aberrant [ 11 C]PK11195 binding and clinical severity. Conclusion: These findings endorse the use of PET imaging with TSPO radioligands as a noninvasive in vivo biomarker of mitochondrial pathology. Classification of Evidence: This study provides Class III evidence that brain PET-MRI with TSPO radioligands identifies mitochondrial pathology.